Creatine Phosphokinase and Visual Analogue Scale as Indicators for Muscle Injury in Untrained Bodybuilders - Shanmugam, Suresh; Farenia, Reni; Tristina, Nina (Althea Medical Journal, 2015)
Background: Skeletal muscle is a vital tissue in the human body to enable breathing, walking and performingÂ several sports activities. However, this muscle is persistently injured throughout every sports session. SomeÂ exercises demand a muscle injury occurrence in order to build a stronger muscle through an adaptationÂ process namely bodybuilding exercise. Importantly, every muscle injury should occur within a physiologicalÂ range which can be identified by several biomarkers as well as pain scale. The aim of this study was toidentify changes on the level of Creatine phosphokinase (CPK) and Visual analogue scale (VAS) between preÂ and post training sessions and the correlation between these two indicators.Methods: This was an observational analytical cross sectional comparison study which was conducted inÂ October 2012 and the subjects were adult untrained bodybuilders at the Jatinangor fitness center. The dataÂ was obtained by measuring serum CPK and marked VAS. The data were analyzed by t-test, Wilcoxonâs testÂ and Spearmanâs correlation.Results: Both CPK and VAS increased significantly by 296 U/L and 19.9 mm respectively. There was a strongÂ positive significant correlation between VAS and CPK (p=0.01, r = 0.711).Conclusion: The healthy untrained bodybuilders chosen in this study experienced a mild (<2000 U/L)Â muscle injury throughout the training sessions with general increased CPK levels and VAS measurement.Â [AMJ.2015;2(1):147â52]